If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -10)(8x + -30) = 180 Reorder the terms: (-10 + 3x)(8x + -30) = 180 Reorder the terms: (-10 + 3x)(-30 + 8x) = 180 Multiply (-10 + 3x) * (-30 + 8x) (-10(-30 + 8x) + 3x * (-30 + 8x)) = 180 ((-30 * -10 + 8x * -10) + 3x * (-30 + 8x)) = 180 ((300 + -80x) + 3x * (-30 + 8x)) = 180 (300 + -80x + (-30 * 3x + 8x * 3x)) = 180 (300 + -80x + (-90x + 24x2)) = 180 Combine like terms: -80x + -90x = -170x (300 + -170x + 24x2) = 180 Solving 300 + -170x + 24x2 = 180 Solving for variable 'x'. Reorder the terms: 300 + -180 + -170x + 24x2 = 180 + -180 Combine like terms: 300 + -180 = 120 120 + -170x + 24x2 = 180 + -180 Combine like terms: 180 + -180 = 0 120 + -170x + 24x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(60 + -85x + 12x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(60 + -85x + 12x2)' equal to zero and attempt to solve: Simplifying 60 + -85x + 12x2 = 0 Solving 60 + -85x + 12x2 = 0 Begin completing the square. Divide all terms by 12 the coefficient of the squared term: Divide each side by '12'. 5 + -7.083333333x + x2 = 0 Move the constant term to the right: Add '-5' to each side of the equation. 5 + -7.083333333x + -5 + x2 = 0 + -5 Reorder the terms: 5 + -5 + -7.083333333x + x2 = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -7.083333333x + x2 = 0 + -5 -7.083333333x + x2 = 0 + -5 Combine like terms: 0 + -5 = -5 -7.083333333x + x2 = -5 The x term is -7.083333333x. Take half its coefficient (-3.541666667). Square it (12.54340278) and add it to both sides. Add '12.54340278' to each side of the equation. -7.083333333x + 12.54340278 + x2 = -5 + 12.54340278 Reorder the terms: 12.54340278 + -7.083333333x + x2 = -5 + 12.54340278 Combine like terms: -5 + 12.54340278 = 7.54340278 12.54340278 + -7.083333333x + x2 = 7.54340278 Factor a perfect square on the left side: (x + -3.541666667)(x + -3.541666667) = 7.54340278 Calculate the square root of the right side: 2.746525583 Break this problem into two subproblems by setting (x + -3.541666667) equal to 2.746525583 and -2.746525583.Subproblem 1
x + -3.541666667 = 2.746525583 Simplifying x + -3.541666667 = 2.746525583 Reorder the terms: -3.541666667 + x = 2.746525583 Solving -3.541666667 + x = 2.746525583 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.541666667' to each side of the equation. -3.541666667 + 3.541666667 + x = 2.746525583 + 3.541666667 Combine like terms: -3.541666667 + 3.541666667 = 0.000000000 0.000000000 + x = 2.746525583 + 3.541666667 x = 2.746525583 + 3.541666667 Combine like terms: 2.746525583 + 3.541666667 = 6.28819225 x = 6.28819225 Simplifying x = 6.28819225Subproblem 2
x + -3.541666667 = -2.746525583 Simplifying x + -3.541666667 = -2.746525583 Reorder the terms: -3.541666667 + x = -2.746525583 Solving -3.541666667 + x = -2.746525583 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.541666667' to each side of the equation. -3.541666667 + 3.541666667 + x = -2.746525583 + 3.541666667 Combine like terms: -3.541666667 + 3.541666667 = 0.000000000 0.000000000 + x = -2.746525583 + 3.541666667 x = -2.746525583 + 3.541666667 Combine like terms: -2.746525583 + 3.541666667 = 0.795141084 x = 0.795141084 Simplifying x = 0.795141084Solution
The solution to the problem is based on the solutions from the subproblems. x = {6.28819225, 0.795141084}Solution
x = {6.28819225, 0.795141084}
| 9w+4=5(w-8) | | (2x+3y)=3x | | 10+6h=34 | | 11x-10=(5x)-(9) | | 11/3=x-4/6 | | 7tanx+3=10tanx | | 1b+94a=94a | | 11x-10=5x-9 | | 5(5+7)=6(X+6) | | 24=(x*7)-(x*3) | | 10x+10y=2 | | 0.2x-2.9=2.9x+2.8 | | 1b+94a=24 | | e^1-5x=37 | | 2(x+6)-7= | | 8(7-1)=-24 | | 21=6g-9 | | 180=x(x-4)(x+9) | | (3c^2d^4)(-2c^2)= | | 0.25-2r=4 | | X(x-4)=4(x-5) | | 2x+46-3x= | | 2g+8=16 | | y+6=-9(x+10) | | 4x(10)2x-2=3x+4 | | a(n)=7+(n-1)(4) | | a(n)=7 | | -6+8(x-4)=12x+3-4x | | y+5=7(x+8) | | x(x+x)=4(4+5) | | .2x^2+12=3.4 | | 5(x+2)=12-3x |